Large-bodied gastric spirurids (Nematoda, Spirurida) predict structure in the downstream gastrointestinal helminth community of wild spiny mice (Acomys dimidiatus) - Jerzy M. Behnke; Joseph A. Jackson; Francis Gilbert; Eman M. E. Mohallal; Anna Bajer (Parasitology, 2024)
The dominant helminths infecting spiny mice (Acomys dimidiatus) in the montane wadis of the Sinai Peninsula of Egypt are spirurid nematodes, notably Protospirura muricola and Mastophorus muris. Both are relatively large robust stomach worms that accumulate in hosts resulting in high worm burdens. To ascertain whether the presence of spirurid worms or their burdens alters the host's likelihood of infection with other helminth species, we analysed a database containing quantitative data on helminth parasites of these mice (n = 431). This comprised of worm burdens recorded during 4 surveys, conducted at 4-year intervals, in 4 wadis, during late summer of each year. The presence of spirurid worms did not significantly alter species richness with other helminth species nor the likelihood of mice carrying other nematode species. However, there was a significant association, particularly of P. muricola, with the presence of intestinal stages of cestodes, and with the acanthocephalan Moniliformis acomysi. After controlling for intrinsic and extrinsic factors, mice harbouring spirurid worms had greater worm burdens of other helminths compared with mice without spirurids. Moreover, spirurid worm burdens showed a significant positive covariation with similarly adjusted species richness of other helminths, non-spirurid helminths, non-spirurid nematodes, oxyuroid nematodes and intestinal stage cestode worm burdens. We interpret these results as an indication that the key driver for co-occurrence of spirurids with other helminths is likely to be transmission via common arthropod hosts (for cestodes and acanthocephalans), but also that mice carrying the heavier spirurid worm burdens become more susceptible to directly transmitted nematodes such as the Oxyuroidea.